180k views
3 votes
Solve the following equation for x: 2x − 3y = 6. x = three halvesy + 3 x = three halvesy − 3 x = negative three halvesy − 3 x = negative three halvesy + 3

2 Answers

3 votes

Answer:

x = three halves y + 3

Explanation:

User Chanafdo
by
5.6k points
4 votes

Answer:


x=(3)/(2)y+3

x = three halves y + 3

Explanation:

we have


2x-3y=6

Solve for x

That means -----> Isolate the variable x

Adds 3y both sides


2x-3y+3y=6+3y


2x=3y+6

Divide by 2 both sides


2x/2=(3y+6)/2


x=(3y+6)/2


x=(3)/(2)y+(6)/(2)


x=(3)/(2)y+3

therefore

x = three halves y + 3

User Fitzilla
by
5.5k points